Among the righteous : lost stories from the Holocaust's long reach into Arab lands - Satloff, Robert 1962- (Public Affairs, 2006)
Introduction : Casablanca's lost story -- From Tunis to Dachau -- The Holocaust's long reach into Arab lands -- Buchenwald in the Sahara -- Nobody told them to do it -- The Arabs watched over the Jews -- Anny's story -- In the heart of Europe -- A crack in the wall